Self-cathing experience journal: Enhancing the patient and family experience in clean intermittent catheterization. Issue 4 (August 2015) - Holland, Jennifer E.; DeMaso, David R.; Rosoklija, Ilina; Johnson, Kathryn L.; Manning, Diane; Bellows, Alexandra L.; Bauer, Stuart B.
Summary: Objective: This pilot study evaluated the safety, feasibility, and usefulness of the Self-Cathing Experience Journal (SC-EJ), an online resource for patients and families to address issues and stigma surrounding clean intermittent catheterization (CIC). Modeled after previous assessments of the Cardiac and Depression Experience Journals (EJs), this project uniquely included patients and caregivers. We explored whether patients and caregivers would find the SC-EJ helpful in increasing their understanding of CIC, accepting the medical benefits of self-catheterization, improving hopefulness, and diminishing social isolation. Methods: Patients seen in a tertiary urology clinic were asked to view the SC-EJ for 30 min and rate its safety and efficacy. The cross-sectional sample included 25 families: 17 surveys were completed by the patient and their caregiver, five by the patient only, and three by the caregiver only. Mean patient age was 15.7 ± 5.8 years (range 7–29 years). The patients were 64% female, and 72% used CIC due to neurological diagnoses. Results: Mean overall patient satisfaction with the SC-EJ was moderately high (mean = 5, out of a 7-point Likert scale from 1 = not at all to 7 = extremely). Mean overall caregiver satisfaction was high (mean = 5.55) and was similar to caregiver satisfaction scores recorded in caregivers with children with congenital heart disease and depression (mean = 5.7 and mean = 5.75, respectively). No significant differences were noted in satisfaction between CIC patients and CIC caregivers or among caregivers of the three populations surveyed (CIC, Cardiac, and Depression). CIC patients and caregivers reported that SC-EJ viewing gave them a strong sense that others are facing similar issues (patient mean = 6.15, caregiver mean = 6.21) and that it was helpful to read about other families' CIC experiences (patient mean = 6, caregiver mean = 5.89). Discussion: The SC-EJ appears to be safe, feasible, and useful to patients and families using CIC. Ratings from caregivers of CIC patients were similar to other cohorts of caregivers facing chronic childhood conditions. Despite beliefs that the EJ format best targets adults, high satisfaction ratings among patients suggest that the SC-EJ is acceptable and beneficial to children and adolescents. This web-based intervention can be a helpful clinical supplement in promoting healthy coping skills and a decreased sense of isolation among patients and families facing CIC. The unique integration of real patient and family experiences with accurate and vetted medical knowledge has the potential to enhance resiliency among viewers who use CIC. Table Mean ratings and SDs for satisfaction and safety of the Self-Cathing Experience Journal by patients and caregivers and comparison of caregiver ratings from the cardiac and depression experience journals. a Patients using CIC ( n = 22) Caregivers of patients using CIC ( n = 20) Mothers of patients with cardiac disease ( n = 40) Caregivers of patients with depression ( n = 35) Comparison of CIC patients and caregivers ( p ) Comparison of caregivers (CIC, cardiac, depression) ( p ) Overall, how satisfied are you with the Self-Cathing Experience Journal? 5 ± 1.17 5.55 ± 1.15 5.7 ± 1.8 5.75 ± 1.66 0.1329 0.9070 Did you feel that the Self-Cathing Experience Journal was hurtful? 1.15 ± 0.37 1.35 ± 1.35 1.2 ± 0.7 1.43 ± 1.14 0.5076 0.6219 Did the Self-Cathing Experience Journal give you any sense that there are others facing similar issues? 6.15 ± 1.18 6.21 ± 1.08 6.7 ± 0.7 6.44 ± 0.91 0.8648 0.1103 Did you find it helpful to read about and see other families' experiences? 6 ± 1.20 5.89 ± 1.24 5.7 ± 1.5 6.06 ± 1.39 0.7718 0.5449 Did the Self-Cathing Experience Journal increase your sense of hope? 4.95 ± 1.70 5.11 ± 1.76 5.1 ± 1.9 5.44 ± 1.42 0.7661 0.6518 CIC = clean intermittent catheterization, used in self-catheterization. a Based on 1–7 Likert scale (1 = not at all, 4 = moderate, 7 = extremely).